THE EFFECTS OF CONCENTRATION PROBIOTIC EFFERVESCENT TABLETS ON THE GROWTH OF Vibrio sp. - Yoswaty, Dessy; Oktavia, Devi Ambarwaty; ', Frisilia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The use of probiotics as an effort to improve the cultivation environment and suppress pathogenic disease proved can help some of the problems in the cultivation of shrimp ponds. This study aimed to determine the effect of the concentration of probiotics effervescent tablets on the growth of Vibrio sp. The method used in the study was an experimental method with 2 treatments, water pond with pond water treatment level is not sterile (non aseptic), pond water that has been sterilized (aseptic) and water pond with bacteria Vibrio sp. and the concentration of probiotics effervescent tablet with a level of treatment 20%, 30% and 40% maltodextrin with 2 repetitions. The ability of probiotics effervescent tablet on the growth of Vibrio sp. it is known to test the TPC (Total Plate Count). Based on the TPC tests have shown that probiotics contained in effervescent tablets with a concentration of 20% maltodextrin has the ability to be most effective in inhibiting or suppressing the growth of Vibrio sp. These indications prove extremely decreasing the amount of bacteria Vibrio sp. on pond water after 48 hours underway. Statistical test result, see from the effect of the concentration of probiotic effervescent tablets on the growth of Vibrio sp. on a shrimp pond water, showed no significant differences (P> 0.05).Keywords: probiotic, effervescent tablets, Vibrio sp., Total Plate Count